2021
DOI: 10.1002/ece3.7840
|View full text |Cite
|
Sign up to set email alerts
|

Coldwater fish in a warm water world: Implications for predation of salmon smolts during estuary transit

Abstract: 1. Predator-prey systems face intensifying pressure from human exploitation and a warming climate with implications for where and how natural resource management can successfully intervene. We hypothesized young salmon migrating to the Pacific Ocean face a seasonally intensifying predator gauntlet when warming water temperature intensifies a multiple predator effect (MPE) from Striped Bass Morone saxatilis and Largemouth Bass Micropterus salmoides. We evaluated this hypothesis using data synthesis and simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 85 publications
(121 reference statements)
1
26
0
Order By: Relevance
“…Munsch et al (2019) found nonsignificant negative correlations between winter precipitation and April water temperatures. Lastly, Nobriga et al (2021) found negative relationships between flow and water temperature on the Sacramento and San Joaquin Rivers within the Delta in April, May, and June.…”
Section: Discussionmentioning
confidence: 98%
“…Munsch et al (2019) found nonsignificant negative correlations between winter precipitation and April water temperatures. Lastly, Nobriga et al (2021) found negative relationships between flow and water temperature on the Sacramento and San Joaquin Rivers within the Delta in April, May, and June.…”
Section: Discussionmentioning
confidence: 98%
“…high temperatures; McCullough, 1999 ) or impact predation rates (e.g. predator species; Nobriga et al, 2021 ), factors that will vary by rearing strategy. Increasing survival for all juvenile rearing strategies would help sustain populations via the portfolio effect ( Sturrock et al , 2020 ; Cordoleani et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although survival during juvenile outmigration decreases as temperature increases ( Michel, 2019 ), the precise temperature-dependent mechanisms impacting survival (e.g. juvenile metabolism, disease, predation rates) are not clear ( Nobriga et al, 2021 ). Future work should quantify survival for other rearing strategies as well as during juvenile outmigration, although we note the difficulty of defining the spatial–temporal movements of juveniles as well as identifying specific runs and populations from juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Striped Bass ( Morone saxatilis ) rarely occur this far upstream, especially in the fall (M. Johnson, CDFW, personal communication, 2020), and the controlled cold‐water dam releases that enable winter‐run egg incubation (Johnson & Lindley, 2016; Martin et al, 2017), likely limit Micropterus sp. occurrence and foraging (Lawrence et al, 2012; Layher et al, 1987; Nobriga et al, 2021).…”
Section: Methodsmentioning
confidence: 99%